2015
DOI: 10.1111/jipb.12423
|View full text |Cite
|
Sign up to set email alerts
|

RNA silencing movement in plants

Abstract: Multicellular organisms, like higher plants, need to coordinate their growth and development and to cope with environmental cues. To achieve this, various signal molecules are transported between neighboring cells and distant organs to control the fate of the recipient cells and organs. RNA silencing produces cell non-autonomous signal molecules that can move over short or long distances leading to the sequence specific silencing of a target gene in a well defined area of cells or throughout the entire plant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 161 publications
(285 reference statements)
2
34
0
4
Order By: Relevance
“…In support of this notion, spraying a 791 nt long noncoding dsRNA (CYP3RNA), which targets the three Cytochrome P450 lanosterol C-14α-demethylase (CYP51) genes FgCYP51A, FgCYP51B and FgCYP51C of Fg strongly inhibited fungal growth on barley leaves. Strikingly, and consistent with the knowledge that sRNA is mobile (Molnar et al 2010;Melnyk et al 2011;Mermigka et al 2016), compromised fungal growth was observed in the directly sprayed (local) as well as the non-sprayed (distal) parts of detached leaves. Efficient spray-induced gene silencing (SIGS) in the distal tissue required: i. passage of CYP3RNA via the plant vascular system, ii.…”
Section: Introductionsupporting
confidence: 59%
“…In support of this notion, spraying a 791 nt long noncoding dsRNA (CYP3RNA), which targets the three Cytochrome P450 lanosterol C-14α-demethylase (CYP51) genes FgCYP51A, FgCYP51B and FgCYP51C of Fg strongly inhibited fungal growth on barley leaves. Strikingly, and consistent with the knowledge that sRNA is mobile (Molnar et al 2010;Melnyk et al 2011;Mermigka et al 2016), compromised fungal growth was observed in the directly sprayed (local) as well as the non-sprayed (distal) parts of detached leaves. Efficient spray-induced gene silencing (SIGS) in the distal tissue required: i. passage of CYP3RNA via the plant vascular system, ii.…”
Section: Introductionsupporting
confidence: 59%
“…It is worth noting that the vascular fungal pathogen V. dahliae takes up large amounts of host-derived sRNAs during infection , which may be due to the location of pathogen colonization. The cell-to-cell movement of RNAi signals through plasmodesmata (PD) and over long distances through the vasculature has been summarized in earlier reviews (Chitwood and Timmermans, 2010;Brosnan and Voinnet, 2011;Mermigka et al, 2016). While cell-to-cell RNAi trafficking is restricted to a limited group of cells, phloem-based movement can transmit RNAi signals to distant organs (Mermigka et al, 2016).…”
Section: Plant Vasculature: a Target Site For Studying Trans-kingdom mentioning
confidence: 99%
“…The cell-to-cell movement of RNAi signals through plasmodesmata (PD) and over long distances through the vasculature has been summarized in earlier reviews (Chitwood and Timmermans, 2010;Brosnan and Voinnet, 2011;Mermigka et al, 2016). While cell-to-cell RNAi trafficking is restricted to a limited group of cells, phloem-based movement can transmit RNAi signals to distant organs (Mermigka et al, 2016). These RNAi signal molecules reach the companion cells of the phloem tissue and then enter sieve elements, which create a conduit for fast transmission to distant organs (Mermigka et al, 2016).…”
Section: Plant Vasculature: a Target Site For Studying Trans-kingdom mentioning
confidence: 99%
“…A remarkable feature of RNA silencing in plants is its non-cell autonomous aspect. In fact, siRNAs move from cell-to-cell through plasmodesmata and their amplification by RDR allows them to reach the phloem and to move systemically [3]. The ability of plants to spread viral siRNAs systemically may play an essential role in antiviral defense.…”
Section: Introductionmentioning
confidence: 99%